KINERJA KEUANGAN PROPERTY DAN REAL ESTATE DIPENGARUHI BEBERAPA VARIABEL DENGAN MODERASI - Winarto, Camelia Kusuma Dewi; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to determine the effect of sales growth, liquidity, and company size on financial performance with profitability as a moderating variable in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This study used 44 companies with a purposive sampling method. This study uses the Microsoft Excel 2016 and Eviews 12 applications. This study shows that sales growth has a positive and not significant effect on financial performance. Liquidity has a positive and significant effect on financial performance. Firm size has a positive and significant effect on financial performance. Profitability that moderates liquidity on financial performance cannot be strengthened.